Koagulopati pada Coronavirus Disease-2019 (COVID-19): Tinjauan pustaka - Herick Alvenus Willim; Amanda Trixie Hardigaloeh; Alice Inda Supit; Handriyani Handriyani (DiscoverSys Inc., 2020)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). COVID-19 has spread globally and become a new pandemic. Although the clinical manifestation of COVID-19 mainly affected the respiratory system, coagulopathy often occurs in the severe cases and is associated with increased mortality. This literature review aims to provide a review of coagulopathy in COVID-19.Methods: This literature review involved 52 relevant literature about coagulopathy and COVID-19. Different data sources or manual literature search methods used to find articles related to the topic of literature.Results: COVID-19 can trigger cytokine storms and systemic hyperinflammation which cause increased activation of coagulation and resulting in hypercoagulability. Hypercoagulability state in COVID-19 increases the risk of thrombosis and thromboembolism, particularly venous thromboembolism. Prophylactic anticoagulants can prevent thromboembolic events and improve the prognosis of COVID-19 patients with coagulopathy.Conclusion: The hypercoagulation state in COVID-19 can increase the risk of complications from thrombosis and thromboembolism, especially venous thromboembolism. Increased D-dimers are a marker of coagulopathy that is often found in patients with severe COVID-19 and is associated with disease severity. Latar Belakang: Coronavirus disease 2019 (COVID-19) merupakan penyakit infeksi akibat severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). COVID-19 telah menyebar secara global dan menjadi pandemi baru. Walaupun manifestasi klinis COVID-19 terutama mengenai sistem respirasi, koagulopati seringkali terjadi pada kasus berat dan berhubungan dengan peningkatan mortalitas. Tinjauan pustaka ini bertujuan untuk memberikan ulasan mengenai koagulopati pada COVID-19.Metode: Tinjauan pustaka ini melibatkan 52 literatur yang relevan tentang koagulopati dan COVID-19. Sumber data yang berbeda atau metode pencarian literatur manual digunakan untuk mencari artikel yang berkaitan dengan topik literatur.Hasil: COVID-19 dapat memicu terjadinya badai sitokin dan hiperinflamasi sistemik yang menyebabkan terjadinya peningkatan aktivasi koagulasi dan mengakibatkan hiperkoagulasi. Keadaan hiperkoagulasi pada COVID-19 meningkatkan risiko terjadinya trombosis dan tromboemboli, terutama tromboemboli vena. Antikoagulan profilaksis dapat mencegah kejadian tromboemboli dan meningkatkan prognosis pada pasien COVID-19 dengan koagulopati.Kesimpulan: Keadaan hiperkoagulasi pada COVID-19 dapat meningkatkan risiko terjadinya komplikasi trombosis dan tromboemboli, terutama tromboemboli vena. Peningkatan D-dimer merupakan penanda koagulopati yang sering ditemukan pada pasien COVID-19 berat dan berhubungan dengan keparahan penyakit.